Digital Contracts and the Challenge of Providing Evidence in Court Under the Indonesian Legal System - Nico Nico; Dianty Savitri; Naufal Afra Munis (PT Publikasiku Academic Solution, 2026)
This study examines the legal position of digital contracts within the Indonesian civil law system, the regulatory framework governing electronic documents and electronic signatures, the evidentiary challenges encountered in court proceedings, and potential solutions to address these challenges. Employing a qualitative descriptive methodology through documentation and literature review, this research analyzes relevant statutory instruments, legal journals, and scholarly sources pertaining to electronic contracts and civil procedure law. The findings reveal that digital contracts in Indonesia are legally recognized under Law Number 11 of 2008 on Information and Electronic Transactions (ITE Law), as amended by Law Number 19 of 2016, along with Government Regulation Number 71 of 2019. These regulations affirm that electronic documents and electronic signatures carry legal evidentiary weight, provided they satisfy prescribed validity requirements. Despite this normative recognition, the evidentiary process in court remains fraught with significant challenges, including concerns over the authenticity and integrity of electronic documents, difficulties in verifying the identities of contracting parties, limited technological literacy among law enforcement officials, inadequate judicial infrastructure for digital evidence examination, and jurisdictional complexities in cross-border digital transactions. To address these challenges, this study recommends continuous regulatory updates, the adoption of advanced security technologies such as encryption and certified digital signatures, capacity-building programs for legal practitioners, strengthened digital forensic systems, and enhanced public awareness regarding safe digital transaction practices. These combined efforts are expected to improve legal certainty and protection for parties engaged in electronic transactions within the Indonesian legal system.